Fresh Produce: Safe Handling Practices for Consumers - Amy Simonne (EDIS)
A healthy diet should include a variety of fruits and vegetables. However, care must be taken to prevent foodborne illnesses that have been traced to some raw fresh produce. Here are steps that you can take to reduce your risk of foodborne illness from fresh produce. This publication is FCS8737, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: November 2002.